Avaliação econômica da produção de camarão (Litopenaeus vannamei) sob a condição de risco no município de Acaraú - estado do Ceará - Dias, Jeronimo Marcelino (2017)
Data from the Food and Agriculture Organization of the United Nations (FAO) indicate that the world's population is expected to reach 8.3 billion by 2030 and the demand for food must keep pace with population growth. The suggestion is for consumption of healthier foods, such as white meat and especially fish, which have proteins of higher biological value and lower amounts of saturated fats. In Ceará, Litopenaeus vannamei shrimp production develops along almost the entire coastline, facilitating the occupation of labor and reducing rural exodus. The Municipality of Acaraú is the second largest shrimp production center in the State of Ceará. From this perspective, it is aimed to analyze economically some rural properties producing shrimp in the Municipality of Acaraú in the State of Ceará. Data of primary nature were collected through the application of questionnaires to a sample of 22 rural producers. We use as methods, the tabular, descriptive analysis and the calculation of economic indicators under both deterministic and risk conditions, being this by the Monte Carlo method. The main conclusion is that all producers have, on average, gross and net positive margins, allowing them to remain in the activity in the short and long term. It is observed that 22.73% of carcinicultors presented losses.